PP14 Adolescents' physical activity. A three-cohort study based on health behaviour in school-aged children (HBSC) Portuguese survey. (21st October 2014) - Marques, A; de Matos, MG
Abstract : Young people's participation in physical activity (PA) is associated with health benefits. However, many young people are not engaging in PA to benefit their health. In order to intervene and reverse this situation, it is important to understand the trends of PA over the years as well as the PA practices of adolescents. This study aimed to investigate the prevalence of physical activity (PA) and understand how it has changed between 2002 and 2010, using three-cohort of representative samples of Portuguese adolescents. Participants were 8483 adolescents (4067 boys, 4416 girls), that participated in the Health Behaviour in School-aged Children (HBSC) Portuguese survey in 2002, 2006 and 2010. A standard questionnaire was used to collected data. ANOVA and chi-square were used to assess the differences among HBSC survey years in each age group. Independent t-tests and chi-square were used to compare adolescents from different cohorts. Analyses were run separately for boys and girls. For the boys, at the age of 15–17 they reported practicing 3.5 ± 1.9 times a week in 2002, 3.9 ± 1.9 in 2006 and 3.8 ± 1.9 in 2010, with a significant increase from 2002 to 2006/2010 (p < 0.05). PA practice during the last 7 days decreased from 4.2 ± 2.1 to 3.9 + 1.9 between 2002 and 2006 (p < 0.001) and decreased 4.4 ± 2.1 to 3.8 ± 1.9 between 2006 and 2010 (p < 0.001). Among girls, PA practices during the last 7 days declined significantly from 3.5 ± 1.9 to 2.7 ± 1.7 between 2002 and 2006 (p < 0.001), and from 3.3 ± 1.9 to 2.9 ± 1.7 between 2006 and 2010 (p < 0.001). The study points to age as a factor related to diminished PA participation. The study also revealed that the prevalence of PA has decreased over the years for the same age groups.